1954
DOI: 10.1139/b54-003
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Respiration of Resting and Germinating Uredospores of Wheat Stem Rust

Abstract: Chemical analyses of wheat stem rust uredospores before and after germination indicated that the lipid fraction was the major endogenous substrate used up during the germination. Some nitrogenous material, presumably protein, was also utilized and increase in chitin was observed during the germination. A number of commercially available metabolic intermediary compounds did not affect the respiration of germinated spores. Heavy metal enzyme inhibitors, such as cyanide and azide, strongly retarded the respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1959
1959
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Our results indicate a role for mannitol as a carbohydrate storage compound because of its rapid disappearance upon germination without ruling out a role in stress protection. There is no doubt that lipids and proteins constitute the major substrates during spore germination (Shu et al, 1954;Bago et al, 1999;Solomon et al, 2003); however, utilizing the pool of mannitol first would enable a quick start of glycolysis, since the conversion of mannitol to Fru is a singleenzyme step. At the same time, oxidation of mannitol to Fru would provide reducing power for anabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a role for mannitol as a carbohydrate storage compound because of its rapid disappearance upon germination without ruling out a role in stress protection. There is no doubt that lipids and proteins constitute the major substrates during spore germination (Shu et al, 1954;Bago et al, 1999;Solomon et al, 2003); however, utilizing the pool of mannitol first would enable a quick start of glycolysis, since the conversion of mannitol to Fru is a singleenzyme step. At the same time, oxidation of mannitol to Fru would provide reducing power for anabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, his observations were largely qualitative in that they were basedl upon the appearance of the fat droplets dturing the various stages in the life cycle. On the other hand, it is fairly wvell estahlishe(d in uredospores of Putcciniia gramiiimis (19) that the saponifiahle fraction of the lipids is reducedl durinig germiination in parallel with the situation in many seedls. By contrast, Ergle (3) has shown that glycogen is the substrate utilized hy sclerotia of Phymatotriclhumii (luriing their germination so that this case, taken together with that of Neurospora ascospores, suggests that the propagules of fungi may utilize endogenouis suhbstrates other than lipids.…”
Section: Activation and Carbohydrate Metabolismmentioning
confidence: 99%
“…The polyol disappeared rapidly from spores during germination indicating a role of this polyol in carbon storage. While there is evidence from other systems that lipids and proteins constitute the major substrates during spore germination (Shu et al 1954;Solomon et al 2003), utilizing the pool of mannitol first would enable a quick start of glycolysis, since the conversion of mannitol to D-fructose is a single enzyme step. At the same time, oxidation of mannitol to D-fructose would provide reducing power for anabolic processes.…”
Section: Biochemical and Molecular Analyses Of Rust Fungimentioning
confidence: 99%